Donor kidney microthrombi and outcomes of kidney transplant: a single‐center experience. (2nd April 2015) - Sood, Puneet; Randhawa, Parmjeet S.; Mehta, Rajil; Hariharan, Sundaram; Tevar, Amit D.
Abstract The kidney wait list has outgrown the supply of available organs every year. Efforts are being made to minimize discard rate of organs. One such area is the use of kidneys with glomerular microthrombi (MT). We retrospectively examined graft/patient outcomes in 28 cases with MT in pre‐implantation biopsies. All patients had follow‐up of at least 36 months, or until graft loss or death. In total, 17 of the 18 patients who underwent follow‐up biopsy within 90 days of transplantation had cleared all MT. Most patients had excellent long‐term graft function. On a closer review of the biopsies included in our study, we found that even in the organs with the most widespread thrombosis, the median percentage of glomeruli with more than 50 percentage of the capillary loops occluded was 8% (range 0–17%). The current practice of mentioning the % of glomeruli with thrombi cannot adequately capture the extent of donor organ pathology, as the actual % glomerular area involved can vary greatly from case to case. Future studies should attempt to quantify donor thrombi by a more robust method and revisit the issue of using clinico‐pathologic parameters to predict allograft function in the setting of MT.